2017
DOI: 10.1074/jbc.m116.755678
|View full text |Cite
|
Sign up to set email alerts
|

(−)-Englerin A-evoked Cytotoxicity Is Mediated by Na+ Influx and Counteracted by Na+/K+-ATPase

Abstract: (−)-Englerin A ((−)-EA) has a rapid and potent cytotoxic effect on several types of cancer cell that is mediated by plasma membrane ion channels containing transient receptor potential canonical 4 (TRPC4) protein. Because these channels are Ca2+-permeable, it was initially thought that the cytotoxicity arose as a consequence of Ca2+ overload. Here we show that this is not the case and that the effect of (−)-EA is mediated by a heteromer of TRPC4 and TRPC1 proteins. Both TRPC4 and TRPC1 were required for (−)-EA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
81
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(88 citation statements)
references
References 24 publications
7
81
0
Order By: Relevance
“…To facilitate cloning of TRPC5‐SYFP2 and TRPC4‐SYFP2, a pcDNA™4/TO expression vector (ThermoFisher Scientific, Waltham, MA, USA), into which a four amino acid linker (ASAS) flanked by AgeI and SacII restriction sites had been introduced between EcoRI and XhoI restriction sites, was used (Naylor et al, ). Human TRPC4β was inserted between BamHI and AgeI restriction sites as described previously (Ludlow et al, ). Human TRPC5 (forward primer: 5′ GCTTGGTACCGCCACCATG 3′ and reverse primer: 5′ TGACACCGGTGAGGCGAGTTGTAACTTGTTCTTC 3′) was inserted upstream of the linker between KpnI and AgeI restriction sites using hTRPC5/pcDNA™4/TO (Zeng et al, ) as a PCR template.…”
Section: Methodsmentioning
confidence: 99%
“…To facilitate cloning of TRPC5‐SYFP2 and TRPC4‐SYFP2, a pcDNA™4/TO expression vector (ThermoFisher Scientific, Waltham, MA, USA), into which a four amino acid linker (ASAS) flanked by AgeI and SacII restriction sites had been introduced between EcoRI and XhoI restriction sites, was used (Naylor et al, ). Human TRPC4β was inserted between BamHI and AgeI restriction sites as described previously (Ludlow et al, ). Human TRPC5 (forward primer: 5′ GCTTGGTACCGCCACCATG 3′ and reverse primer: 5′ TGACACCGGTGAGGCGAGTTGTAACTTGTTCTTC 3′) was inserted upstream of the linker between KpnI and AgeI restriction sites using hTRPC5/pcDNA™4/TO (Zeng et al, ) as a PCR template.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Beech et al suggested that Na + /K + ATPase inhibitors such as ouabain may synergize with englerin A in the proper context. 66 In the NCATS study mentioned above, a modest amount of synergy was seen with proscillaridin, but not with ouabain in Ewing’s sarcoma cells. Such synergies justify in vivo combination studies to guide future clinical therapy and may inform mechanistic studies of all compounds involved.…”
Section: Preclinical Studiesmentioning
confidence: 92%
“…65 A recent report from Beech’s group found that englerin A cytotoxicity was mediated by influx of sodium, rather than of calcium, as had been previously proposed, and that both TRPC4 and TRPC1 must be part of the ion channel complex for cytotoxicity. 66 …”
Section: Mechanism Of Action Studiesmentioning
confidence: 99%
“…Mutations of TRP channels cause various inherited diseases in the cardiovascular, renal, skeletal, and nervous system. Among them include chronic pain and overactive bladder (TRPV1), diabetes (TRPV1, TRPM4), Alzheimer's disease (TRPM7), and cancer (TRPC4/C1, TRPC6, TRPV2, and TRPM8) (14,97).…”
Section: Transient Receptor Potential (Trp) Channelsmentioning
confidence: 99%
“…However, one of the most widely expression systems, which is used to study the electrophysiological, pharmacological, and biophysical properties of ion channels is oocytes from the Xenopus laevis. There are numerous advantages to use Xenopus oocytes as an expression system to study ion channels, such as maintaining Xenopus laevis is cost effective, their large size eases the injection of heterologous cRNA and the experiments (14,15). Certainly, there are also several disadvantages to use oocytes as an expression system.…”
Section: Technical Considerationsmentioning
confidence: 99%